Как понимаются заголовки новостей? К вопросу кликбейта: К вопросу кликбейта - Bibok, Károly (SlavVaria, 2024)
How to (re-)interpret titles of news? Case studies of clickbaits. The present paper investigates titles of Russian and Hungarian news items in pragmatic frameworks definitely emerging in recent years (FINKBEINER 2024). It shows a claim that the understanding of news headlines should proceed considering the texts themselves. What is more, the body of the text does inevitably figure as a necessary context for the understanding. A qualitative analysis of headlines recovers a wider spectrum of (re-)interpretation compared to the paper by V. Apresjan and A. Orlov (APRESJAN, ORLOV 2022). To illustrate the novelty of my approach, two examples taken from their paper are submitted to a thorough revision. (For other types of (re-)interpretation applied during my qualitative analysis of headlines, see BIBOK 2024.)